Penerapan Strategi Discovery Learning pada Pembelajaran Sejarah Kebudayaan Islam Kelas X IPS di MAN Lakitan - Lukman Hakim; Rika Fitri; Ernayenti Ernayenti; Toni Nasution (Journal on Education, 2023)
The purpose of this study is to describe the implementation of Islamic cultural history learning using discovery learning strategies. The form and type of this research is field research using descriptive qualitative methods. Data collection techniques through observation, interviews and documentation. The data sources are in the form of primary data and secondary data. The primary data are religious teachers who have used discovery learning strategies in learning the history of Islamic culture, while the secondary data are the Principals and Administration of MAM Lakitan. The data analysis technique that the writer uses is data reduction, data presentation and conclusion. Learning the history of Islamic culture using the Discovery Learning Strategy Religion teachers are required to design an implementation plan before teaching by the Principal, the implementation of learning can bring maximum results, but Religion teachers experience problems in implementing learning so Religion teachers must try to overcome the obstacles encountered in learning cultural history Islam by using the Discovery Learning Strategy in class X IPS at MAM Lakitan.